INFRARED-ABSORPTION AND MICROWAVE INFRARED DOUBLE-RESONANCE STUDIES OF NE.OCS MOLECULAR-BEAMS - Hayman, G; Hodge, J; Howard, B; Muenter, J; Dyke, T (1987)
Infrared absorption spectra for molecular beams of Ne·OCS have been observed with a diode laser for the vibrational transition near 2062 cm -1 correlating with the monomer ν3 mode. The linewidths were ∼150 MHz (FWHM), giving rotationally resolved spectra and allowing the upper and lower vibrational state A, B, and C rotational constants to be determined along with the frequency of the band origin. No broadening in excess of that expected from Doppler effects and laser linewidth was observed, setting a lower limit of 10-9 s on the lifetime of the upper state. Rotational transitions for the vibrational ground state were observed by microwave-infrared double resonance experiments. The ∼150 kHz linewidths in these experiments increased the precision of the rotational constants and permitted the quartic centrifugal distortion constants for the ground state to be determined. The effective structure of the Ne·OCS complex was calculated from the rotational constant data. The vibrational frequency and structural results are discussed in relation to similar work on other rare gas-OCS complexes. © 1987 American Institute of Physics.